ANALISIS KEBIJAKAN MONETER TERHADAP JUMLAH UANG BEREDAR DI INDONESIA - Bandi, Herly Marlina; Maria Indriyani Hewe Tiwu,; Rikhard T. Ch. Bolang, (Journal of Innovation Research and Knowledge, 2026)
This study aims to analyze the impact of monetary policy, specifically open market operations and the discount facility, on the money supply (M2) in Indonesia. Using time-series data and multiple linear regression, the study evaluates the partial and simultaneous effects of these monetary instruments. The results show that open market operations have a positive and significant influence on the money supply, while the discount facility has a negative and significant effect. Simultaneously, both instruments significantly affect M2, with an Adjusted R² of 53.45%. These findings highlight the effectiveness of Bank Indonesia’s monetary policy in managing liquidity and maintaining macroeconomic stability.